Designing and Constructing a Novel Artificial Pathway for Malonic Acid Production Biologically - Gu, Shuying; Zhao, Zhen; Yao, Yonghong; Li, Jingen; Tian, Chaoguang (Frontiers in Bioengineering and Biotechnology, 2022)
Malonic acid is used as a common component of many products and processes in the pharmaceutical and cosmetic industry. Here, we designed a novel artificial synthetic pathway of malonic acid, in which oxaloacetate, an intermediate of cytoplasmic rTCA pathway, is coverted to malonic semialdehyde and then to malonic acid, sequentially catalyzed by α-keto decarboxylase and malonic semialdehyde dehydrogenase. After systematic screening, we discovered the enzyme oxaloacetate decarboxylase Mdc, catalyzing the first step of artificial designed pathway in vitro. Then, this synthetic pathway was functionally constructed in cellulolytic thermophilic fungus Myceliophthora thermophila. After enhancement of glucose uptake, titer of malonic acid achieved 42.5 mg/L. This study presents a novel biological pathway for producing malonic acid from renewable resources in future.